Circulating tumor DNA-guided treatment decision in metastatic castration-resistant prostate cancer patients: a cost-effectiveness analysis - Catharina J. P. Op ’t Hoog; Sabien J. E. Bosman; Emmy Boerrigter; Niven Mehra; Inge M. van Oort; Nielka P. van Erp; Wietske Kievit (Therapeutic Advances in Medical Oncology)
Background: The androgen receptor pathway inhibitors (ARPI), abiraterone acetate and enzalutamide, are commonly used in first-line treatment of patients with metastatic castration-resistant prostate cancer (mCRPC). However, early resistance to ARPI treatment occurs frequently. Traditionally, the response is evaluated 3–6 months after the start of treatment. However, recent findings indicate that by detecting circulating tumor DNA (ctDNA) at baseline and 4 weeks after ARPI treatment initiation, patients with a nondurable response can be identified after 4 weeks of treatment, enabling an early switch to alternative treatments. Objective: This study aims to evaluate the cost-effectiveness of ctDNA-guided treatment switch after 4 weeks of ARPI therapy in mCRPC patients compared to standard of care. Design: A cost-effectiveness analysis. Methods: A cost-effectiveness analysis was conducted by creating a Markov state transition model to simulate progression, mortality, and treatment costs over a 5-year time horizon comparing ctDNA-guided care versus standard of care. The outcomes measured were incremental treatment costs per life-years and quality-adjusted life-years (QALYs) gained. Results: The analysis showed an incremental cost-effectiveness ratio of €65,400.86 per QALY gained and an incremental net monetary benefit of €2716.62. Thereby, the use of ctDNA-guided treatment was cost-effective in comparison to standard care in 74% of the simulations using a willingness-to-pay threshold of €80,000 per QALY gained. Conclusion: Our study demonstrated the cost-effectiveness of using a ctDNA-guided early therapy switch in non-responders after only 4 weeks of first-line ARPI therapy in mCRPC patients. This paves the way for implementing ctDNA-guided treatment decisions in clinical practice.